1992
DOI: 10.1007/bf02245486
|View full text |Cite
|
Sign up to set email alerts
|

Drug discrimination studies in rats with caffeine and phenylpropanolamine administered separately and as mixtures

Abstract: The discriminative stimulus effects of mixtures of caffeine and phenylpropanolamine (PPA) have been investigated because these drugs have been abused together. Rats were trained to discriminate caffeine (20 mg/kg), PPA (20 mg/kg), or a mixture of both drugs, from saline in a two-bar operant conditioning procedure with food reinforcers presented on a tandem VI-FR schedule. Discriminations of mixture, caffeine alone and PPA alone were 90% accurate after 40 sessions. Generalisation to both PPA and caffeine was we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Approximately 60 and 40 % drug-appropriate responding was attained when tested with 1 mg / kg of FEN and PHEN, respectively. When the data was subjected to the predictive tests as described by Mariathasan and Stolerman (1992), the predicted drug-appropriate response for the discriminative e¤ect of the mixture was very similar (76 %) to that of the actual dose-response curve (82%). The data for the overall rates of lever responding indicated some additive e¤ects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 60 and 40 % drug-appropriate responding was attained when tested with 1 mg / kg of FEN and PHEN, respectively. When the data was subjected to the predictive tests as described by Mariathasan and Stolerman (1992), the predicted drug-appropriate response for the discriminative e¤ect of the mixture was very similar (76 %) to that of the actual dose-response curve (82%). The data for the overall rates of lever responding indicated some additive e¤ects.…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary observations along with those in obese patients suggest that the mixture of PHEN and FEN may be working synergistically, an approach which could be implemented in the treatment of other compulsive disorders. Synergistic drug interactions have been reported with some combinations of drugs using the drug discrimination paradigm (Mariathasan and Stolerman 1992).…”
Section: Introductionmentioning
confidence: 99%
“…injection of either saline vehicle (vol ¼ 0.01 ml/g) or 5, 10, and 40 mg/kg PPA. These doses of PPA are in the range of those used previously to examine the behavioral or neurochemical effects of PPA in adult rodents (Eisenberg et al, 1987;Mariathasan and Stolerman, 1992;Mittleman et al, 1993;Rushing et al, 1993;McMahon and Wellman, 1996). As PPA is an anorectic (eg, Eisenberg et al, 1987;Mittleman et al, 1993;Wellman, 1990), body weight was recorded daily before each injection.…”
Section: Subjectsmentioning
confidence: 99%
“…Whereas PPA does not elicit locomotor hyperactivity in rats or maintain self-administration behavior in monkeys trained to selfadministered cocaine (Eisenberg et al, 1987;Mittleman et al, 1993;Woolverton et al, 1986), it substitutes for amphetamine in rat self-administration studies (Wellman et al, 1989). Moreover, PPA substitutes for illicit psychomotor stimulants in drug discrimination studies employing both human and nonhuman primates, as well as rodents (Chait et al, 1988;Lee et al, 1989;Mariathasan and Stolerman, 1992;Woolverton et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Garcha and Stolerman (1989) reported the absence of generalization to either morphine or phencyclidine in rats trained to discriminate a mixture of nicotine plus midazolam and suggested that using mixtures of drugs for training does not necessarily weaken the pharmacological speciÞcity of discriminations. When a test drug has discriminative e¤ects that resemble those of one training drug, partial or full generalization may occur (Mariathasan and Stolerman 1992;Harrison et al 1998). The extent of such generalizations can also depend upon the doses of drugs used for training; thus, generalization from a mixture of amphetamine plus pentobarbitone to apomorphine was greater at small than at large training doses .…”
Section: Introductionmentioning
confidence: 98%